2018
DOI: 10.1002/jum.14770
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Characteristics of Foot and Ankle Structures in Healthy, Coper, and Chronically Unstable Ankles

Abstract: The ultrasound protocol proved reliable and was used to evaluate the length, thickness, and cross-sectional areas of selected ankle structures. The length of the ATFL and the thickness of the ATFL and calcaneofibular ligament were longer and thicker in injured groups compared to healthy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 44 publications
1
13
0
1
Order By: Relevance
“…More research is necessary in this way. Recent research of Abdeen et al compared ankle structures injured and non-injured in LAS, concluded no statistically significant differences between health injured tendon and muscles ankle with the injured, these results are similar as our findings (45).…”
Section: Non-association Between Tendon Ligament and Joint Conditions And Atfl Injurysupporting
confidence: 92%
“…More research is necessary in this way. Recent research of Abdeen et al compared ankle structures injured and non-injured in LAS, concluded no statistically significant differences between health injured tendon and muscles ankle with the injured, these results are similar as our findings (45).…”
Section: Non-association Between Tendon Ligament and Joint Conditions And Atfl Injurysupporting
confidence: 92%
“…The thickening of the CFL has been considered to be a significant morphologic parameter of an inflammatory hypertrophic CFL. However, Abdeen et al reported that ultrasound (US)-guided CFLT diagnostic sensitivity and specificity were 47% and 83%, respectively, with an accuracy of 72% (24). Moreover, we found several difficulties associated with measuring CFLT.…”
Section: Discussionmentioning
confidence: 61%
“…Several studies have explored the possible correlation between ATFL structural changes and ankle joint stability. Some investigators (14) have found that injured ATFLs were longer and thicker than healthy ATFLs. Other researchers (16) have shown that chronic ankle sprain patients have a significantly greater ATFL area than control subjects.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the vast majority of studies have focused on ATFL morphological changes (13)(14)(15)(16), including changes to ligament thickness, length, width, continuity, and crosssectional area. Several studies have explored the possible correlation between ATFL structural changes and ankle joint stability.…”
Section: Introductionmentioning
confidence: 99%